Colombian Prototype of a Spirometer, From Classroom to Practice - Imbachi-Diaz, Aliz A.; Tobar, Jose Aramid Chaves; Perea, Jose Dario; Santacruz Almeida, Luis Andres (International Journal of STEM Education for Sustainability, 2023)
Design technological tools from basic sciences would be an excellent way for students to learn about Science, Technology, Engineering, and Mathematics (STEM) applications. Nowadays, young people are more connoisseurs of computer tools and gadgets than other generations. They could use those aptitudes with correct stimulation and orientation to generate new knowledge or improve technological applications in developing countries like Colombia. Designing or improving technology starting from basic knowledge and developing cheap technology is essential for the development of a society. We used a case study in this work, due to COVID 19 pandemic, we propose the design and creation of a prototype of a spirometer started from a class activity to put into practice the knowledge acquired in theoretical class and let students observe and implement physics applications. As a result, elemental physics course students achieve testing it on real people and compare it with known results. The students' spirometer prototype was made with inexpensive implements starting with the knowledge learned in the classroom. With it, students tried it on actual patients, letting them get measurable data consistent with known results from the literature. These experiences increased students' interest in science and its applications. This work shows us that applying STEM methodology from basic levels to practical uses could motivate young people to learn and improve their skills in those topics and see science as a way of life.